Association between plant-based dietary patterns and dementia among Chinese older adults - Xian, Xiaobing; Chen, Yue; Fu, Yandi; Chen, Ziyi; Xiang, Jie; Han, Ze; Zeng, Li; Li, Jiaxia; Wang, Yuanyuan; Shen, Kun (Frontiers in Nutrition, 2025)
BackgroundDementia has become a major concern with the rapid aging of the population. While plant-based dietary habits are widely regarded as beneficial, evidence on their associations with dementia among Chinese older adults is still limited.MethodsOur study included 9,360 individuals from the 2018 data collection of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), a nationally representative, cross-sectional survey. We developed three plant-based diet indices—the overall (PDI), healthful (hPDI), and unhealthful (uPDI)—using a simplified food frequency questionnaire. Multivariable logistic regression, adjusted for various covariates, was used to examine the associations between these diet indices and dementia prevalence. Additional analyses encompassed restricted cubic splines (RCS), subgroup analyses, interaction tests, and sensitivity analyses to assess the robustness of the findings. We further validated the results in an independent group of 588 older adults from Chongqing, China.ResultsThe observed prevalence of dementia among older adults in the CLHLS sample was 10.67%, while a cross-sectional survey conducted in Chongqing reported a prevalence of 13.78%. Results from logistic regression models controlling for all covariates indicated that the PDI, hPDI, and uPDI were significantly associated with dementia among Chinese older adults (PDI: OR = 0.964, 95% CI = 0.951–0.977; hPDI: OR = 0.976, 95% CI = 0.963–0.990; uPDI: OR = 1.012, 95% CI = 1.001–1.024). The restricted cubic spline (RCS) analysis further confirmed a significant dose-response relationship between PDI, hPDI, and dementia. Interaction analysis revealed that diabetes and physical exercise significantly modified these associations. Validation results based on the older adult population in Chongqing were consistent with the above findings.ConclusionPlant-based dietary patterns showed significant cross-sectional associations with dementia prevalence among Chinese older adults. The modifying effects of diabetes and exercise highlight the importance of considering individual characteristics when examining diet–dementia relationships.